REVAMPING THE CONDITIONS OF AWAITING TRIAL INMATES IN NIGERIA: EXPERIENCE FROM KWARA STATE CORRECTIONAL FACILITIES (Journal of Governance and Development (JGD), 2025)
The paper aims to gauge the perceptions of awaiting trial inmates across correctional facilities in Kwara State, Nigeria. This research also intends to uncover the state or conditions of inmates awaiting trial in relation to the statutory functions of correctional services as stipulated in the Nigerian 1979, 1989, and 1999 constitutions as amended, as well as other reforms on the criminal justice act. The methodology adopted for this research purpose was the descriptive survey design method. Data collection procedures consisted of both primary and secondary materials sources. Principal information was collected by administering questionnaire forms to inmates awaiting trial, while the secondary data consisted of the internet, websites, journals published theses, etc. The study revealed that corruption, favoritism, poor hygiene, hard labor, and health issues have major challenges across correctional facilities. It was also discovered that there are no clear-cut differences in the treatment and handling of convicted criminals from inmates awaiting trial in correctional facilities. The study recommended improvement in conditions of service for correctional officers. It also advocates for the adoption of information and communications technology (ICT) within correctional facilities, and there should be segregation of convicted criminals from awaiting trial inmates, among other recommendations. This study will no doubt contribute to existing knowledge in criminal justice systems and will help countries know the antecedent effect of increased awaiting trial on correctional facilities, their staff, state security, and government expenditure and, finally, how it could be addressed.